Preparation and Characterization of Mixed Ligands of Flucloxacillin and Proline and Theoretical Treatment to Form Coordination Complexes with Some Metal Ions - abd alhadi, shayma; Hassan , Sahar S. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2025)
Flucloxacillin (Flx) derivative metal complexes(2S,5R,6R)-6-({[3-(2-chloro-5-fluorophenyl)-5-methylisoxazol-4-yl] carbonyl}amino)-3,3-dimethyl-7-oxo-4-thia-1-azabicyclo [3.2.0] heptane-2-methyl aster and proline with CoII, NiII, CuII, ZnII and CdII. They were synthesized and identified using physicochemical techniques, including elemental analysis CHNS, metal analysis AA, Uv-Vis, FTIR, TGA, magnetic susceptibility, and conductivity measurement. This study aims to investigate the coordination behavior of flucloxacillin and proline, analyze their structural and electronic properties, and evaluate their potential biological activities against bacterial and fungal strains. Additionally, theoretical calculations using HyperChem software are conducted to assess the stability and electronic configurations of the synthesized complexes. Flucloxacillin reacted with metal ions as a bidentate ligand using the nitrogen of the β-lactone thiazolidine ring and the carboxylate ion, forming a five-membered ring, according to the results and from the oxygen and amine group of proline as mixed ligand complexes, with a six-coordination octahedral geometry proposed for all complexes. The Hyper Chem-8.0.7 software was employed to compute the Heat of Formation (Hf), Binding Energy (∆Eb), Total energy (∆ET), Vibration Spectra, and Electronic Spectra for the mixed ligand and its corresponding metal complexes. The antifungal activity of mixed ligands and their metal complexes was evaluated against Candida albicans, while their antibacterial activity against Staphylococcus aureus and Escherichia coli was also assessed. These tests were conducted at a concentration of 5 mM in a nutritional agar medium.